Evaluating sub-Saharan Africa's electrification progress: Guiding principles for pro-poor strategies. (May 2021) - Tarekegne, Bethel; Sidortsov, Roman
Abstract: Energy access rates improved significantly in developing nations in the past decade. However, sub-Saharan Africa still remains with the highest percentage of its population in energy poverty. The diversity of technologies and business models available today offer promise to expanding access for the region. Nonetheless, past energy related inequities point to the key role institutional norms and planning standards play in shaping the consequences of electrification efforts beyond the technologies or the business models employed. For the sub-Saharan Africa region, where country budgets are limited, multilateral organizations and their financial resources remain the critical institutions that set the standards that guide the region's electrification efforts. Through a socio-legal research methodology, the paper applies the energy justice concept as an analytical lens to assess the existing standards and frameworks in the region's energy access planning and decision-making processes. Using energy sector project finance appraisal documents as case studies, we reveal the equity limitations and gaps in the status quo process. The study finds that, although the presence of development finance institutions plays a role in advancing energy access for all, the standards that guide their actions can perpetuate planning processes that generate inequitable outcomes on people and their capabilities. The study provides guiding principles for a just and informed standard for energy access planning.